Construction of New Norms for the Implementation of Fines in Narcotics Cases in Indonesia - Bakhtiar, Bakhtiar; Din, Mohd; Yunus, Ilyas; Darmawan , Darmawan (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2026)
Narcotics abuse constitutes a violation of statutory regulations, particularly Article 7 of Law No. 35 of 2009 on Narcotics, which restricts the use of narcotics to health services and the advancement of science and technology. Narcotics abuse may result in serious consequences not only for individuals but also for society, especially the younger generation. In Indonesia, narcotics misuse has spread across all levels of society, from lower to upper classes. Apart from causing dependency, narcotics consumption frequently leads to death. This circumstance poses a significant threat to the sustainability of society, the nation, and the state, placing Indonesia in a state of narcotics emergency. Accordingly, the Narcotics Law prescribes stringent sanctions, including the death penalty, imprisonment, and fines as additional or substitute penalties for convicted offenders. This study examines the imposition of fines as a substitute for imprisonment and explores judicial considerations in delivering such decisions. The study employs a normative legal method. Findings reveal that convicted persons tend to prefer imprisonment to paying fines, mainly because the fines imposed are excessively high and beyond their financial capacity. As a result, the potential state revenue from fines is not realized, while the state must instead bear substantial expenses to maintain prisoners during their incarceration. Therefore, a reconstruction of legal norms is necessary to achieve a more proportional and effective regulation of fines and imprisonment.